مستوى الطموح لدى عينة من تلاميذ المرحلة الثانوية و علاقته ببعض المتغيرات - بيبي, مرزاق; نيس, حكيمة (جامعة الوادي University of Eloued, 2017)
الملخص: هدفت الدراسة إلى الكشف عن مستوى الطموح لدى عينة من تلاميذ المرحلة الثانوية، والكشف عن الفروق تبعا لمتغيرات الجنس و المستوى الاقتصادي للأسرة و المستوى التعليمي للوالدين ، من خلال إجراء دراسة ميدانية على عينة مقدرة ب 52 تلميذ و تلميذة من ثانويات مقاطعة قمار بالوادي وباستخدام مقياس الطموح معد من طرف الباحثة.أظهرت النتائج وجود مستوى متدني إلى متوسط للطموح لدى تلاميذ المرحلة الثانوية، وباستخدام الاختبار"ت" لدراسة الفروق تبين:- وجود فروق ذات دلالة إحصائية في درجات مستوى الطموح لدى تلاميذ المرحلة الثانوية تبعا لمتغير الجنس، المستوى الاقتصادي للأسرة. المستوى التعليمي للوالدين.. وخلصت في الأخير إلى جملة من المقترحات أهمها: ضرورة اعتماد منهج التكامل بين المؤسسات الاجتماعية والتربوية المختلفة (الأسرة، المدرسة،الجامعة، المسجد،وسائل الإعلام..) في أداء رسالتها لتكوين مواطن صالح. التركيز على أهمية البناء الروحي والقيمي للفرد إلى جانب البناء المعرفي. The study aimed to detect the level of ambition in a sample of secondary school students, and to detect the differences according to the variables of sex, the economic level of the family, the educational level of the parents and, through conducting a field study on an estimated sample of 52 students and secondary schoolgirls The results showed a low to average level of aspiration among secondary school students. Using the "T" test for the study of the differences revealed: There were statistically significant differences in the level of ambition of secondary students according to the variable For sex, age. Economic level of the family. Educational attainment of parents Finally, she concluded with a number of proposals, the most important of which is the necessity of adopting the integration approach between the various social and educational institutions (the family, the school, the university, the mosque, the media) in the performance of its mission to form a good citizen.
دراسة ميدانية بولاية الوادي
مقال
Keywords: مستوى الطموح; الجنس، ; المستوى الاقتصادي للأسرة; المستوى التعليمي للوالدين; تلميذ المرحلة الثانوية; Level of ambition, gender, economic level of the family, educational level of parents, secondary school student